Insane city [compact disc, unabridged] - Barry, Dave (Penguin Audio, 2013)
Seth Weinstein knew Tina was way out of his league in pretty much any way one could imagine, which is why it continued to astonish him that he was on the plane now for their destination wedding in Florida. The Groom Posse had already sprung an airport prank on him, and he'd survived it, and if that was the worst of it, everything should be okay. Smooth sailing from now on. Seth has absolutely no idea what he's about to get into. It's not smooth sailing, it's more like a trip on the Titanic.